(3JLQjO GdGYJbGOs
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGLH GdhLhO aEfi Edi eG SFdJ ajg ef JMQjQ eSGFd GdcdGe GdebUO GdChd ai GdCehQ GdYGeI hajg aUhd GdaUd GdChd ai GdhLhO hGdYOe s
(3BNQgG (B:s
(3hGdfSb GdNQhL Yf WGYI Gddg JYGdi eY GdEjeGf hGdCeQ HGdeYQha GdhGLH hGLH hcPG Gdfgi Yf GdefcQ Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3GdfSNI HgG MhGTs
(3Ydjg MGTjI HgG cJGH aGQSis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJhMjO hGdedd hGdfMds